World map of low-layer atmospheric extinction values for solar power tower plants projects. (December 2022) - Salmon, Aloïs; Marzo, Aitor; Polo, Jesús; Ballestrín, Jesús; Carra, Elena; Alonso-Montesinos, Joaquín
Abstract: Atmospheric extinction is defined as the ability of the atmosphere to attenuate the solar radiation beam. In the case of concentrating solar power tower plants, low-layer atmospheric extinction plays an important role in the assessment of the solar resource by attenuating the radiation on its way from the heliostats to the receivers. The lack of values of the low-layer atmospheric extinction could lead to incorrect decisions in solar projects and investments. In this paper, we present a world map of annual low-layer atmospheric extinction values. The world map has been elaborated by processing the 30-year database provided by MERRA-2 and the use of atmospheric radiative transfer codes. The results show that the atmospheric extinction values are not negligible and reach high values in many areas of the sun belt. Global daily averages of atmospheric extinction are between approximately 3% and 30%, implying the similar values of annual energy losses in solar power tower plants. The southern hemisphere is characterised by low extinction values, while hight attenuation values are found in the northern hemisphere, especially in West and Central Africa, the Arabian Peninsula, Turkmenistan, India, and China, where annual atmospheric extinction exceeds 20%, reaching values of 30% in some places. These results have a major impact on the economic evaluation of solar tower projects. For atmospheric extinction values above 20%, the impact on the Levelized Cost Of Energy implies upward corrections of more than 25%, approaching 50% for values such as those obtained in Chat or Niger. Geographical information of low-layer atmospheric extinction values will help to reduce uncertainty margins in studies related to tower technology solar plants.